No Significant Association Between the Fecal Microbiome and the Presence of Irritable Bowel Syndrome-type Symptoms in Patients with Quiescent Inflammatory Bowel Disease. Issue 7 (13th April 2018) - Shutkever, Oliver; Gracie, David J; Young, Caroline; Wood, Henry M; Taylor, Morag; John Hamlin, P; Ford, Alexander C; Quirke, Philip
Abstract: Background: The microbiome is implicated in the pathogenesis of inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS). Whether a distinct microbiome profile is associated with the reporting of IBS-type symptoms in IBD patients is uncertain. We aimed to resolve this issue using a cross-sectional study design. Methods: Using clinical disease activity indices, the Rome III criteria for IBS and fecal calprotectin levels, we divided IBD patients into 4 groups: IBS-type symptoms, quiescent disease, occult inflammation, and active disease. A16S rRNA microbiome analysis was performed to determine whether any taxa were differentially abundant, and whether there were any differences in alpha or beta diversity in patients reporting IBS-type symptoms compared with those in the other 3 groups. Results: Of 270 patients included, 70 (25.9%) had IBS-type symptoms, 81 (30.0%) quiescent IBD, 66 (24.4%) occult inflammation, and 53 (19.6%) active IBD. At phylum level, there was a nonsignificant increase in the abundance of Actinobacteria in patients reporting IBS-type symptoms, but no other differences at any taxonomic level. When compared with patients reporting IBS-type symptoms, mean alpha diversity was greater in patients with quiescent disease, although this was nonsignificant (28.6 vs 31.7, P = 0.33), and similar to those with occult inflammation and active disease. Beta diversity variation among the 4 groups was significant for unweighted ( P = 0.002) but not weighted ( P = 0.21) UniFrac analysis. Conclusions: Reporting IBS-type symptoms was not associated with distinct microbiome alterations. Unmeasured confounding could have impacted the significance of our findings.